Smoking Status and Cessation Counseling Practices Among Physicians, Guangxi, China, 2007 - Jiatong Zhou, MD; Abu S. Abdullah, MD, PhD; Vivian C. Pun, MPH; Dongmei Huang, MD; Songyi Lu, MD; Shuiying Luo, MD (Preventing Chronic Disease, 2010)
IntroductionWe examined Chinese physicians’ smoking behavior, knowledge of smoking’s health effects, and compliance with accepted cessation counseling practices.MethodsWe used a structured questionnaire adapted from the Global Health Professionals Survey of the World Health Organization to survey Chinese physicians based at 5 hospitals in Nanning, Guangxi Province, China.ResultsThe response rate was 85% for a total of 673 completed questionnaires. Of the 673 respondents, 73% were men, 42% were aged 30 years or younger, and 26% were smokers (men, 35%; women, 3%). Only 28% of the smokers were ready to quit immediately. A substantial proportion of physicians did not have adequate knowledge of smoking-related health hazards or favorable attitudes toward smoking cessation counseling. Asking patients whether they smoked and recording smoking status in the medical record were significantly associated with being female and being very well or somewhat prepared to counsel patients about smoking cessation. Advising patients to quit smoking was significantly associated with being female, being a nonsmoker, being very well or somewhat prepared to counsel patients about smoking cessation, and having read any smoking cessation guidelines.ConclusionsOur findings suggest that smoking is common among male Chinese physicians and that Chinese physicians have inadequate knowledge of smoking’s health hazards and of how to help smokers quit. Physicians in China and their patients who smoke would benefit from widely accessible Chinese clinical practice guidelines on smoking cessation, better medical school education about the health risks of smoking, and government funding of cessation medications.